An Analysis of Perception and Financial Planning Behaviour for Retirementamong Working Individuals - R, MS.VIJAYALAKSHMI.; SUDHA, DR. B (The journal of contemporary issues in business and government, 2021)
Purpose: Although the financial planning for retirement is a complex and multifaceted process for any employed individual, much of the existing research only examines retirement planning in the lines of factors that influence savings for the future, perception of individuals, role of financial planners and also impact of debt level with respect to retirement planning. As the global pandemic storm wreaked havoc in almost every sector of the economy, a more comprehensive understanding on the financial planning for retirement and in particular the discipline of holding on to the plan was considered imperative to be studied. The research also involved understanding the perception of the individuals regarding asset allocation preferred for retired life, priority in terms of financial planning and the impact of various factors affecting the behaviour of adhering to the financial planning for retirement for which Social Cognitive Theory was used as a conceptual base. The empirical study has followed a questionnaire based survey research on employed individuals. Data from 202 participants were analysed using various tools like Descriptive Statistics, Chi Square Analysis, Kendall’s Coefficient of Concordance W, Exploratory Factor Analysis and Multiple Regression. The collected data were analysed using SPSS 20.0. The study revealed that an individual’s financial planning for retirement behaviour is highly influenced by external environmental factors.